2001
DOI: 10.1016/s0735-1097(01)01635-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for secundum atrial septal defects in patients >40 years old

Abstract: We prospectively examined whether surgical treatment of secundum atrial septal defects (ASDs) in patients > or =40 years old improves their long-term clinical outcome. Surgical treatment of secundum ASDs in adults > 40 years old is a subject of controversy because of the perception of good long-term clinical outcomes in patients with unrepaired ASDs and the lack of data from randomized trials. We recruited 521 patients > 40 years old with secundum ASDs referred for treatment; 48 were excluded. Patients were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(57 citation statements)
references
References 23 publications
1
55
0
1
Order By: Relevance
“…More recently, a randomized study to either medical treatment or surgical ASD closure for NYHA I or II patients Ͼ40 years old demonstrated that surgical closure decreased the occurrence of long-term major cardiovascular events, primarily because of a decrease in the incidence of recurrent pneumonia. 19 Our results confirm the limitations of clinical evaluation of functional class in a chronic disease. Rostagno et al 20 showed in his study of chronic heart failure patients that concordance between NYHA classification and levels of performance using cardiopulmonary exercise testing was Ͻ50%.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, a randomized study to either medical treatment or surgical ASD closure for NYHA I or II patients Ͼ40 years old demonstrated that surgical closure decreased the occurrence of long-term major cardiovascular events, primarily because of a decrease in the incidence of recurrent pneumonia. 19 Our results confirm the limitations of clinical evaluation of functional class in a chronic disease. Rostagno et al 20 showed in his study of chronic heart failure patients that concordance between NYHA classification and levels of performance using cardiopulmonary exercise testing was Ͻ50%.…”
Section: Discussionsupporting
confidence: 82%
“…The ostium secundum type of atrial septal defect (ASD II) is the most common congenital heart defect diagnosed in adults and makes up 40% of acyanotic shunt heart disease in individuals over the age of 40 years [1,2,3]. Because of the mostly asymptomatic course of the disease, ASD sometimes goes unrecognized until the later decades of life [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Only 50% of the affected population survives until the age of 50 years and the annual mortality rate in persons older than 50 years reaches 6–7% [3, 4]. Over time the left-to-right atrial shunt increases and pulmonary pressure becomes higher, resulting in a right ventricular load increase [1, 6]. Debate on optimum ASD management in adulthood remains open.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, we can avoid complications of open heart surgery, which is absolutely crucial in the group of patient with insignificant shunt. Another benefit is avoidance of a surgical scar commonly called by psychologists a “scar of the human soul” and shorter hospitalization time [8, 9]. It allows even percutaneously, the closure of the ASD in the patients with insignificant shunt is controversial.…”
Section: Discussionmentioning
confidence: 99%